2019
DOI: 10.15405/epsbs.2019.04.72
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Place's Capital As An Instrument Of Innovative Development Of The Region

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Earlier, we showed that "the totality of significant elements (meanings) of the territorial environment that provide the local place with recognition, fame, prestige, and credibility from various social groups" represents the symbolic capital of the place (Fedotova, 2018, p. 144). Moreover, the value of symbolic capital is measured by the effect (symbolic profit) that it brings to its owner, while being converted into economic benefits" (Eldieva, Fedotova, &Zhukov, 2019, p. 682). https://doi.org/10.15405/epsbs.2019.12.05.86 Corresponding Author: N. G. Fedotova Selection andpeer-review under…”
Section: A City Brand As a Symbolic Capital Of A Placementioning
confidence: 99%
“…Earlier, we showed that "the totality of significant elements (meanings) of the territorial environment that provide the local place with recognition, fame, prestige, and credibility from various social groups" represents the symbolic capital of the place (Fedotova, 2018, p. 144). Moreover, the value of symbolic capital is measured by the effect (symbolic profit) that it brings to its owner, while being converted into economic benefits" (Eldieva, Fedotova, &Zhukov, 2019, p. 682). https://doi.org/10.15405/epsbs.2019.12.05.86 Corresponding Author: N. G. Fedotova Selection andpeer-review under…”
Section: A City Brand As a Symbolic Capital Of A Placementioning
confidence: 99%